Emblem of ruin: the fate of allegory in a time of weak theory. Issue 10 (3rd October 2021) - Nyerges, Aaron
ABSTRACT: This article assesses the place of allegory in a literary field influenced by weak theory. As an ancient form of expression that encrypts ulterior meanings, allegory requires claims that would seem to supersede the restricted and descriptive methods of contemporary criticism. Drawing from the oeuvre of Walter Benjamin and setting it to work through the art collection of the Hollywood icon Mary Pickford, I argue that allegory's respect for deterioration can actually support the restrictedness of critical claims, and that its image of ruin provides a strong emblem for weak theory.